Needs identification methodology for inclusive design. Issue 4 (2nd April 2016) - Blasco, R.; Blanco, T.; Marco, A.; Berbegal, A.; Casas, R.
ABSTRACT: Identification of user needs is an essential phase in the early stages of every design project. Many needs identification methodologies are described in the literature. When targeting users with special needs, the task becomes more challenging for different reasons (difficulty of retrieving information, performing prototype testing, etc.). This article presents a novel methodology, Needs Identification Methodology for Inclusive Design (NIMID), that guides the process of needs identification in the inclusive design scenario considering users' physical, sensorial and cognitive capabilities. NIMID is grounded in Abowd and Beale's human–computer interaction framework and uses WHO's International Classification of Functionalities as the taxonomy that provides a common language. We exemplify the application of the methodology in the design of a smart oven for elderly people. We also compare NIMID with other methodologies evidencing its strong points: universality (common international classification of functioning language), systematicity (clearly defined phases and outcomes) and rationality (grounded in well-established interaction theory).